A Glance at Archives of Academic Emergency Medicine Journal in 2024 - Yazdanbakhsh, Mehrnoosh; Saghaei Dehkordi, Somayeh (Archives of Academic Emergency Medicine, 2024)
There were 70 articles published in the 2024 volume of Archives of Academic Emergency Medicine. Around 350 authors contributed to the published works, who were affiliated to centers located in countries such as USA, Canada, Germany, Finland, China, Poland, Italy, Australia, UAE, Malaysia, India, Egypt, Bangladesh, Turkey, Thailand, Nigeria, Jordon, Yemen, Saudi Arabia, Azerbaijan, Vietnam, Pakistan. We would like to thank the authors for trusting us with their valuable works and publishing their articles with us.